2018
DOI: 10.12928/telkomnika.v16i2.8416
|View full text |Cite
|
Sign up to set email alerts
|

Driver Behaviour State Recognition based on Speech

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The discriminative model, however, computes the conditional probability distribution p(B d |X ) to analyze which driving behavior class B d the input data set X belongs to. Support vector machine (SVM) [172], k-nearest neighbors (kNN) [173], fuzzy logic system (FLS) [174], logistic regression [175], conditional random fields (CRFs) [176], deep artificial neural networks (ANN) such as multi-layer perceptron (MLP) [177], convolutional neural network (CNN) [178], recurrent neural network (RNN) [179], reinforcement learning (RL) models [180] etc., are among this model. To enhance the prediction capability, some studies used hybrid techniques.…”
Section: Data-driven Behavior Modelsmentioning
confidence: 99%
“…The discriminative model, however, computes the conditional probability distribution p(B d |X ) to analyze which driving behavior class B d the input data set X belongs to. Support vector machine (SVM) [172], k-nearest neighbors (kNN) [173], fuzzy logic system (FLS) [174], logistic regression [175], conditional random fields (CRFs) [176], deep artificial neural networks (ANN) such as multi-layer perceptron (MLP) [177], convolutional neural network (CNN) [178], recurrent neural network (RNN) [179], reinforcement learning (RL) models [180] etc., are among this model. To enhance the prediction capability, some studies used hybrid techniques.…”
Section: Data-driven Behavior Modelsmentioning
confidence: 99%
“…Tang et al [14] proposed a novel lane change detection mechanism called FCMNN, which is based on the combination of Fuzzy C-means clustering algorithm and adaptive neural network. Kamaruddin et al [15] detected the driver behavior based on emotions collected from speech using a combination of MFCC and MLP. Hu et al [16] identified the driver activities such as using a mobile phone, talking with passengers, and smoking from still images using a deep learning multi-stream convolutional neural network approach.…”
Section: Prior Workmentioning
confidence: 99%
“…Arduino Uno can be activated via a USB connection or with an external power supply [23]. The power source is selected automatically [24]. This microcomputer has 14 digitals I/O port (six of them can provide the PWM outputs), 6 analog I/O ports, a reset switch and a ISP download [25].…”
Section: Arduino Unomentioning
confidence: 99%